Activation of 2‐Cyclohexenone by BF3 Coordination: Mechanistic Insights from Theory and Experiment. (23rd March 2021) - Peschel, Martin T.; Kabaciński, Piotr; Schwinger, Daniel P.; Thyrhaug, Erling; Cerullo, Giulio; Bach, Thorsten; Hauer, Jürgen; de Vivie‐Riedle, Regina
Abstract: Lewis acids have recently been recognized as catalysts enabling enantioselective photochemical transformations. Mechanistic studies on these systems are however rare, either due to their absorption at wavelengths shorter than 260 nm, or due to the limitations of theoretical dynamic studies for larger complexes. In this work, we overcome these challenges and employ sub‐30‐fs transient absorption in the UV, in combination with a highly accurate theoretical treatment on the XMS‐CASPT2 level. We investigate 2‐cyclohexenone and its complex to boron trifluoride and analyze the observed dynamics based on trajectory calculations including non‐adiabatic coupling and intersystem crossing. This approach explains all ultrafast decay pathways observed in the complex. We show that the Lewis acid remains attached to the substrate in the triplet state, which in turn explains why chiral boron‐based Lewis acids induce a high enantioselectivity in photocycloaddition reactions. Abstract : The Lewis acid complex of 2‐cyclohexenone and BF3 relaxes to the active triplet state after photoexcitation in less than a picosecond. This process can be followed by XMS‐CASPT2 dynamics and transient absorption spectroscopy.